Strong patronage, weak parties the case for electoral system redesign in the Philippines - Hutchcroft, Paul D. (Anvil Publishing, 2019)
Electoral system redesign : an opportunity for effective political reform in the Philippines -- Paul D. Hutchcroft Why (and how) electoral systems shape development outcomes -- Allen Hicken Designing and reforming electoral systems in Southeast Asia -- Benjamin Reilly When does electoral system reform occur? -- Allen Hicken Gender and the electoral system : what works for women -- Socorro L. Reyes Lessons from a neighbor : the negative consequences of Indonesia's shift to the open list --Edward Aspinall The Political Party Development Bill : strengthening parties toward the goal of strengthening Philippine democracy -- Ramon C. Casiple Patronage politics and parties in the Philippines : insights from the 2016 elections -- Meredith L. Weiss Untangling the party list system -- Julio C. Teehankee The multi-member plurality system in the Philippines and its implications --Nico Ravanilla.